Outcomes of incisional hernia using laparoscopic sutured abdominal wall reconstruction - Dung, Tran Ngoc; Phan, Nguyen Duc; Anh, Nguyen Ngoc; Dung, Luu Quang; Vinh, Nguyen Thi Thu; Tu Anh, Nguyen; Van, Nguyen Quoc; Ha, Hoang Ngoc; Cuong, Truong Van (Tạp chí Nghiên cứu Y học, 2025)
Incisional hernia (IH) is a common condition after major abdominal surgeries. To date, surgery particularly laparoscopic techniques is the primary treatment, offering several advantages. This study aims to describe the surgical technique and evaluate outcomes of laparoscopic sutured abdominal wall reconstruction for IH at Hanoi Medical University Hospital. A retrospective descriptive study was conducted on 11 patients treated from 2019 to 2024. The male-to-female ratio was 3:8, with a mean age of 57.4 ± 12.1 years old (range: 41 - 79 years old). The main symptom prompting medical consultation was the appearance of an abdominal mass at the site of a previous surgical incision, with no case of strangulation complications. The mean hernia defect width was 6.2 ± 1.8cm with the largest measuring 10cm and the smallest 4cm. The mean operative time was 69.1 ± 36.6 minutes (range: 30 - 120 minutes), with no recorded intraoperative complication. The average postoperative hospital stay was 1.8 ± 0.98 days (range: 1 - 4 days). No case of chronic pain or recurrence were reported during the follow-up period of 18 - 24 months. Laparoscopic sutured abdominal wall reconstruction for the treatment of IH is a safe and effective surgical method with minimal complications and a low recurrence rate.